Analisis Post-Traumatic Growth pada Atlet Cedera Kronis: Tinjauan dari Aspek Psikologis - Isnan Rahmat Wiyata; Muhammad Thoriq Hadad Akbar; Amin Brilian Wicaksono Gussanto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
ABSTRACT This study aimed to examine psychological skills and post-traumatic growth (PTG) among athletes experiencing chronic sports injuries. A mixed-methods design was employed involving 95 athletes from various sports. Quantitative data were collected using the Post-Traumatic Growth Inventory (PTGI) and the Psychological State Inventory for Sports (PSIS), while qualitative data were obtained through semi-structured interviews. The results indicated that athletes with chronic injuries maintained moderate to high levels of psychological skills, with motivation and self-confidence emerging as dominant components. Athletes also reported meaningful levels of PTG, particularly in the domain of relating to others. Correlational analysis revealed a very strong positive relationship between psychological skills and PTG. Qualitative findings further showed that acceptance, social support, and positive meaning-making played a crucial role in psychological adaptation. These findings suggest that chronic sports injury does not inevitably result in psychological decline, but may serve as a context for psychological growth when supported by adequate mental skills and a supportive social environment. Conclusion, The results of this study indicate that athletes who experience chronic sports injuries are able to maintain adaptive psychological function and show significant post-traumatic growth. Keywords: post-traumatic growth, psychological skills, chronic injury, athletes, rehabilitation .